Unraveling the Enigma of Anti-Tubercular Drug-Induced Vitamin B6 Deficiency and its Role in Provoking Convulsive Seizures: A Revelatory Case Report - Utpal Bhui; Subhajit Sarkar; Joy Das; Indra Kumar Ghoshal; Abhik Saha; Bimlesh Kumar (Indian Journal of Pharmacy & Drug Studies, 2023)
The 65-year-old female patient with active tuberculosis who was hospitalized to the primary hospital and was on Category 1 Antitubercular Drugs (Cat 1 ATD) is the subject of this case report. The patient had complications, a reduced appetite, had stopped eating, was nauseous, and had vomited. Eight months prior, the patient has prescribed the first-line anti-tubercular medications rifampin, rifabutin, ethambutol, and isoniazid. Three months prior, the patient stopped taking the medicine. Now, as a result of an unfavorable drug reaction to anti-tubercular medications, the patient had acquired acute hepatitis and convulsive seizuresdue to vitamin B6 deficiency.